THE EFFECT OF GRAMMAR MASTERY AND LEARNING MOTIVATION ON ENGLISH SPEAKING ABILITY - Amrullah, Kunah (STIT Buntet Pesantren Cirebon, 2022)
Speaking is one of important parts in teaching language because it includes one of four basic language skills. That skill is taught to students in order to be able to use English in real communication. The quality of a person's communication depends on the quantity and quality of the use of grammar. Besides being able to understand of grammar, learning motivation is also very important. Students who have high learning motivation are very influential on high speaking ability. Otherwise, students who have low motivation have an effect on low speaking ability. Therefore, those factors are common problems faced by students where the students are not actively engaged in a speaking activity. And that happened to students of class XI at SMAN 1 Losarang and SMAN 1 Kandanghaur, Indramayu district. This problem motivated the researcher to investigate the effect of grammar mastery and learning motivation on students' speaking ability. The subjects in this study were 75 students of class XI. The instrument used was multiple choice with 20 questions for the variable of mastery of grammar and a questionnaire with 30 questions used Scala Likert for the variable of learning motivation. The inference analysis used is descriptive correlational research and multiple linear regression. The results showed that there was a significant effect of mastery of grammar and motivation to learn together on the ability to speak English, this is evidenced by the acquisition of Sig. = 0.000 < 0.05 and F observe = 60,468 . There is a significant effect grammar mastery towards the ability to speak English, this is evidenced by the acquisition of Sig. = 0,04 <0,05 and T observe = 2,089. 3) There is a significant effect of learning motivation towards the ability to speak English, this is evidenced by the acquisition of Sig. 0,000 <0,05 and T observe = 5,586. The study concluded that with students had good mastery of grammar and high learning motivation certainly had a big influence on students' speaking abilities, especially in English.